To Examine The Effect Of Financial Conditions, Company Growth, And Company Size On Going Concern Audit Opinions In Manufacturing Companies Listed On The Indonesia Stock Exchange - Ima Andriyani; Amrillah Azrin; Kusminaini Armin; Agustina Marzuki (Best Journal of Administration and Management, 2023)
This study aims to examine the effect of financial conditions, company growth, and company size on going concern audit opinions in manufacturing companies listed on the Indonesia Stock Exchange. Issuing a going concern audit opinion is very useful for users of financial statements to make the right investment decisions, because when an investor wants to make an investment he needs to know the financial condition of the company itself, especially concerning the survival of the company. This study uses a combination method, namely a combination of qualitative and quantitative. This study also uses secondary data, with documentation data collection techniques. The population in this study is 26 manufacturing companies listed on the (IDX). Researchers used non-probability sampling method. Data were tested using descriptive statistical tests, classical assumption tests, logistic regression analysis, regression model feasibility tests, overall model tests, hypothesis testing, and the coefficient of determination. The results of this study are as follows: 1) Simultaneously Financial Condition, Company Growth, and Company Size have a significant effect on Going concern Audit Opinion 2) Partially Financial Condition has a significant effect on Going concern Audit Opinion. 3) Partially, company growth has a significant effect on going concern audit opinion. 4) Partially, company size has no significant effect on going concern audit opinion. So that future researchers can use other variables besides those that the researchers examined, in order to realize even better research.